DIGITAL TRANSFORMATION IN ISLAMIC FINANCIAL INSTITUTIONS WITH CHALLENGES AND OPPORTUNITIES FOR SHARIA-COMPLIANT ACCOUNTING SYSTEMS - Eddy, Pujiono; Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Tanjung, Amries Rusli; Musa, Sulaiman (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to explore the dynamic interplay between digital transformation and the operational, regulatory, and ethical dimensions of a Shariah-compliant accounting system. A descriptive-exploratory design was used to investigate the current state of digital transformation in IFIs and analyze the integration of digital accounting technologies in the context of Shariah compliance. A purposive sampling technique will be used to select participants with relevant experience and expertise in Islamic finance and digital systems. Interview data will be transcribed and analyzed using thematic analysis. The study findings reveal that while digital innovations, such as AI, cloud computing, and blockchain, are being embraced in customer-facing services, their implementation in core accounting and Shariah governance functions remains limited (Wati et al., 2024). This study contributes to the growing literature on Islamic digital finance by highlighting the need for a distinct theoretical framework that integrates Islamic accounting principles with digital transformation models. Future studies could use quantitative methods to measure the impact of digital transformation on financial performance or customer satisfaction in Islamic banks. Studi ini bertujuan untuk mengeksplorasi interaksi dinamis antara transformasi digital dan dimensi operasional, regulasi, dan etika dari sistem akuntansi yang sesuai dengan Syariah. Desain deskriptif-eksploratori digunakan untuk menyelidiki keadaan transformasi digital terkini di IFI dan menganalisis integrasi teknologi akuntansi digital dalam konteks kepatuhan Syariah. Teknik pengambilan sampel purposif akan digunakan untuk memilih partisipan dengan pengalaman dan keahlian yang relevan dalam keuangan Islam dan sistem digital. Data wawancara akan ditranskripsi dan dianalisis menggunakan analisis tematik. Temuan studi mengungkapkan bahwa sementara inovasi digital, seperti AI, komputasi awan, dan blockchain, dianut dalam layanan yang berhadapan dengan pelanggan, implementasinya dalam fungsi akuntansi inti dan tata kelola Syariah masih terbatas (Wati et al., 2024). Studi ini berkontribusi pada literatur yang berkembang tentang keuangan digital Islam dengan menyoroti perlunya kerangka teoritis yang berbeda yang mengintegrasikan prinsip-prinsip akuntansi Islam dengan model transformasi digital. Studi masa depan dapat menggunakan metode kuantitatif untuk mengukur dampak transformasi digital pada kinerja keuangan atau kepuasan pelanggan di bank-bank Islam.